Integrating Digital Literacy into Biology Learning to Improve High School Students' Critical Thinking Skills - Ahmad Robith Firdausi; Robby, Nur Satriya; Kustiana (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2025)
This study aims to analyze the effectiveness of integrating digital literacy into Biology learning to enhance senior high school students’ critical thinking skills. Digital literacy, as a 21st-century competence, encompasses the ability to access, evaluate, and process information through technology in an ethical manner. In Biology learning, the integration of digital literacy is expected to foster students’ critical thinking through the exploration of interactive resources, data analysis, and the formulation of scientific arguments. The method used in this research was a quasi-experimental design with a Non-Equivalent Control Group. The research subjects consisted of two grade XI science classes selected purposively: the experimental group received Biology instruction based on digital literacy (interactive simulations, online journal analysis, infographic creation), while the control group was taught using conventional methods (lectures, discussions, manual experiments). Data were collected through critical thinking skill tests administered during the pre-test and post-test stages. The results showed that the average pre-test scores of both groups were nearly the same (62.5 and 63.1). After the treatment, the experimental group’s average score significantly increased to 82.7 (gain score 20.2), while the control group reached only 70.3 (gain score 7.2). The t-test revealed a significant difference between the two groups (t=6.45; p=0.000). In conclusion, the integration of digital literacy in Biology learning proved to be more effective than conventional methods in improving students’ critical thinking skills. This study highlights the importance of teachers systematically integrating digital literacy with adequate digital infrastructure support in schools